Ocena vrednosti kmetijske proizvodnje v Republiki Sloveniji - Vrišer, Igor (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2005)
The report is an attempt to estimate the agricultural production value in Slovenia on the basis of estimation districts and geographical regions. The report is based on data of harvest and production, collected by Statistical Office of Slovenia within the "Census of agricultural farming in the year 2000", and on the average purchase price for some agricultural products, which were registered in the department of agricultural statistics at the Statistical Of. ce in the year 2003. The results should indicate territorial difference in the agricultural production value.
Keywords: agriculture; kmetijstvo; raba tal; agrarna geografija; kmetijska proizvodnja; produktivnost; Slovenia; Slovenija